Pendampingan LKS Tematik SD Khas Budaya Masyarakat Kota Wisata Batu Jawa Timur - Restian, Arina; Amelia, Delora Jantung; Saputra, Setiya Yunus (Universitas Darussalam Gontor, 2019)
Implementation, a community service program entitled